The narrows : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch, 2004)
When an infamous serial killer known as the Poet reemerges, FBI agent Rachel Walling, long haunted by her unsuccessful efforts to bring him to justice, receives assistance from LAPD detective Harry Bosch.